Analisis kadar protein dan uji hedonik pada cookies berbasis tepung singkong dan tepung kacang hijau sebagai alternatif pmt untuk stunting - Aulia, Khairunnisa; Kisnawaty, Sudrajah Warajati; Kurnia, Pramudya (Poltekkes Kemenkes Aceh, 2025)
Background: Malnutrition in infants and children, especially those under five years old, can hinder physical and mental growth. The Indonesian Nutritional Status Survey (SSGI) reported that the prevalence of stunting in Indonesia in 2024 is 19,8%. Protein plays a role in the regeneration of damaged cells as well as the formation of important enzymes and hormones in the body. Cookies are a popular snack among the public, thus chosen as a medium for innovative nutritional intake for children in the form of Supplementary Feeding.Objectives: This study is to determine the most preferred cookie formulation with the highest protein content, which could serve as an alternative supplementary food to help prevent stunting in children.Methods: This research employed an experimental design using a Completely Randomized Design (CRD) to examine differences among cookie formulations and identify the best one. Four formulations are tested: 100% wheat flour (control), 75% cassava flour and 25% mung bean flour, 50% cassava flour and 50% mung bean flour, and 25% cassava flour and 75% mung bean flour. Organoleptic tests assessed appearance, aroma, color, taste, texture, and overall acceptability using a 5-point hedonic scale. The sensory evaluation involved 30 children as panelists. Protein content was analyzed using the Kjeldahl method at the Food Quality Analysis Laboratory of Universitas Muhammadiyah Surakarta. Data were analyzed using SPSS and Excel to identify significant differences among formulations.Results: Among the four formulations tested (F1, F2, F3, and F4), it was found that the highest protein content was in F3 (11,62%) with a cassava flour to mung bean flour ratio of 50:50, while in the hedonic evaluation, Formula 3 received the highest average score for the taste attribute (4.46) and was the most preferred after the control (F1) in the overall attribute (4,40).Conclusion: The best formulation was F3, with a protein content of 11,62%, the highest among all samples. Although F3 ranked second in the acceptance test, after the control (F1), it holds strong potential as an alternative locally based supplementary food (PMT) due to its nutritional value.